Engineering orbital coupling in rare-earth-doped layered double hydroxides for enhanced wound healing - Jiajia Jing; Yan Miao; Xiaotong Ma; Ruichen Wang; Haojie Wei; Chuxuan Liu; Kelong Fan; Jingping Zhong; Haifeng Liu (Chemical Engineering Journal, 2026)

Dynamic social disparities in the U.S. electric vehicle charging infrastructure system - Ruichen Ma; Mingming Guan; Dingkang Teng; Xiong Yang; Chengxiang Zhuge (Transportation Research Part D: Transport and Environment, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Postharvest application of plasma-activated water to extend shelf life of strawberries - Yingman Gao; Yupan Zhu; Panfeng Guan; Leiyi Zhang; Xinyue Li; Guihuan Wei; Chenbin Hu; Ruichen Sha; Nanshan Du; Ruonan Ma; Zhen Jiao; Bing Li (Food Chemistry, 2026)

3D porous cellulose/polyaniline aerogel composite as a high-performance electrode for selective electrosorption of rhenium - Ruichen Ma; Boxiao Zhao; Xiling Sun; Zhenning Lou; Junshuo Cui; Haibiao Yu; Yuejiao Wang; Weijun Shan; Xiaogeng Feng; Ying Xiong (Water Research, 2026)

A global insight into integration of metro and electric vehicle charging stations - Dingkang Teng; Justin Hayse Chiwing G. Tang; Ruichen Ma; Xiong Yang; Chengxiang Zhuge (Sustainable Cities and Society, 2026)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Rice cultivation and its environmental and social contexts at the Shimao site, Northwest China - Shu Liu; Ruichen Yang; Zhouyong Sun; Jing Shao; Zhikun Ma (Archaeological and Anthropological Sciences, 2025)

Do small block treatments matter in block identification for rock block system mechanical analysis? - Zheqi Tian; Jun Zheng; Xiaochu Peng; Qing Lü; Ruichen Zhang; Xianchun Ma; Jianhui Deng (Computers and Geotechnics, 2024)

Spatial heterogeneity analysis on distribution of intra-city public electric vehicle charging points based on multi-scale geographically weighted regression - Ruichen Ma; Ailing Huang; Hongyang Cui; Rujie Yu; Xiaojin Peng (Travel Behaviour and Society, 2024)

MPM-based mechanism and runout analysis of a compound reactivated landslide - Kun He; Chuanjie Xi; Bo Liu; Xiewen Hu; Gang Luo; Guotao Ma; Ruichen Zhou (Computers and Geotechnics, 2023)

Rapid Characterization of Landslide-Debris Flow Chains of Geologic Hazards Using Multi-method Investigation: Case Study of the Tiejiangwan LDC - Kun He; Bo Liu; Xiewen Hu; Ruichen Zhou; Chuanjie Xi; Guotao Ma; Mei Han; You Li; Gang Luo (Rock Mechanics and Rock Engineering, 2022)

Reconstruction of catastrophic outburst floods of the Diexi ancient landslide-dammed lake in the Upper Minjiang River, Eastern Tibetan Plateau - Junxue Ma; Jian Chen; Zhijiu Cui; Wendy Zhou; Ruichen Chen; Chengbiao Wang (Natural Hazards, 2022)

Prevention of acetaminophen-induced hepatocyte injury: JNK inhibition and GSTA1 involvement - Yicong Chang; Jingshan He; Bingke Ma; Muhammad Ishfaq; Jiaqi Wang; Ruichen Zhang; Liang Yuan; Jiarui Liu; Changwen Li; Fangping Liu (Molecular & Cellular Toxicology, 2021)